The impact of digital economy on China’s green-oriented transition of energy: multiple mediation effects from a spatial perspective - Hou, Jianchao; Ye, Shuying (Frontiers in Energy Research, 2024)
With the continuous advancement of the new generation of information technology revolution, digital economy is gradually becoming an important driving force for energy transition while restructuring the new form of the economy. This paper selects panel data of 30 provinces in China from 2011 to 2021, empirically verifies the special impacts of digital economy on green-oriented transition of energy by using the spatial Durbin model, and further constructs a multi-intermediary model to verify its transition pathways. The main findings are as follows: First, the overall level of green-oriented transition of energy in China's eastern coastal areas is relatively high, and the western regions have been more capable of catching up in recent years. Second, digital economy has played a significant role in promoting greenoriented transition of energy, and there is a positive spatial spillover effect. Third, digital economy could indirectly promote the green-oriented transition of energy by promoting the upgrading of industrial structure, improving the level of technological innovation and strengthening environmental regulations. This study provides empirical insights and reference for policy makers in accelerating the comprehensive green-oriented transition of energy.